Development of E-Modules Based on Socio-Scientific Issues to Improve The Creative Thinking Skills of High School Students - Cholivatus Sa'diah; Purwanto, Andik; Koto, Irwan (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
The research aims to develop e-modules based on socio-scientific issues that are feasible to use, determine the response of grade X students to the use of e-modules based on socio-scientific issues and determine the increase in creative thinking of grade X students. This development research is based on the 4-D model which includes four steps namely Define, Design, Develop, Disseminate. This research was conducted until the Develop stage due to the limited time of researchers in conducting research. The subjects of this study were 33 grade X students. The instruments used were expert validation assessment sheets, student response questionnaires and creative thinking skills test questions. The results of this study indicate that e-modules based on socio-scientific issues are very feasible to use because the use of e-modules can improve students' creative thinking skills with an average percentage of 91%. Students' creative thinking skills obtained an N-Gain value of 0.76 (high category). Students' response to the e-module based on socio-scientific issues is included in the very good category because this e-module presents subject matter and explanatory videos on each topic and improves students' creative thinking skills with an average percentage of 87%. Based on these results, it can be concluded that the e-module based on socio-scientific issues developed is very feasible to use.